PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN MOTIVASI BERPRESTASI WARGA BELAJAR PROGRAM PENDIDIKAN KECAKAPAN HIDUP - Iis Prasetyo; Sutaryat Trisnamansyah (Jurnal Ilmiah Visi, 2011)
This study aimed to develop a model of problem-based learning to increase the achievement motivation of the participants of life skills education programs and to examine the effectiveness of the learning model in accelerating the achievement motivation. The research conducted in Kemloko, Srimartani village, Piyungan Sub-district, Bantul, in the Province of Yogjakarta, employed research and development approach in an oyster mushroom cultivation training. The try out of the model used experimental design (quasi experiment - a non equivalent control group design), with 20 people for each group. The results showed that there is no difference in achievement motivation scores before and after training (p = 0.385) in the control group after an average of different test score achievement motivation, while there are differences in achievement motivation scores before and after training (p = 0.001). Effectiveness test also showed significant differences between the control and treat-ment groups (p = 0.012) so that the problem-based learning model is effective to increase achievement motivation compared to the conventional models (model control class).